Marketing in school environments: the youth marketing industry perspective - Geraci, John (Henry Stewart Talks, 2010)
How do those working in youth fields view today's youth generation?, Targeting young people as consumers, Commercialism in schools, Why do educators want corporations?, Why do corporations want to reach kids in schools?, What forms does school marketing take?, Arguments in support of commercialism in schools, The case against, The youth industry's views towards marketing in schools, How industry can get on the right side of this issue